The newly proposed dietary index for gut microbiota and its association with the risk of nonalcoholic fatty liver disease: the mediating role of body mass index - Shengnan Meng; Luonan Li; Shijie Yin; Yuxuan Zhao; Yaning Liu; Yuxi Zhang; Xiaolin Zhang; Fengxue Yu (Diabetology & Metabolic Syndrome)
Abstract Background and aims Nonalcoholic fatty liver disease (NAFLD) is strongly associated with dietary habits and the gut microbiota. The dietary index for the gut microbiota (DI-GM) is a newly proposed index that reflects gut microbial diversity based on dietary intake. However, its relationship with NAFLD remains unclear. This study aimed to explore the association between DI-GM and the risk of NAFLD. Methods In this cross-sectional study, we utilized data from the NHANES 2009–2018. Multivariable logistic regression, restricted cubic spline curves (RCS), subgroup analysis, and mediation analysis were used to evaluate the association between DI-GM and the risk of NAFLD. Results A total of 4,923 participants were included in the study. According to the fully adjusted model, a significant inverse association was observed between DI-GM and NAFLD (OR = 0.883, 95% CI: 0.835–0.932, P < 0.001). After stratification by quartiles, compared with participants in the first quartile of DI-GM score, those in the fourth quartile had a 36.5% lower odds of developing NAFLD (OR = 0.635, 95% CI: 0.481–0.839, P = 0.002). Mediation analysis revealed that 72.69% of the association between DI-GM and NAFLD was mediated by BMI (P < 0.001). Subgroup analysis suggested that the association between DI-GM and NAFLD might be influenced by race (P for interaction < 0.05). RCS analysis revealed a linear correlation between DI-GM and NAFLD (P for nonlinear = 0.883). Conclusions DI-GM is negatively associated with NAFLD risk, with BMI mediating this relationship and race being a significant influencing factor.